2020
DOI: 10.1039/c9cc09103c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic kinetic resolution of a tertiary alcohol

Abstract: The first example of a dynamic kinetic resolution of a racemic tertiary alcohol is presented. By combining a lipase-catalyzed kinetic resolution and a racemization with an oxovanadium-catalyst, the ester was obtained in 77% yield and with >99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The construction of tertiary alcohols bearing different carbon substituents is challenging and has a potential role in biological applications. 50,51 With this in mind, we are interested in studying the hydrolytic ring-opening of spiro-epoxyoxindoles that lead to the formation of differently substituted alcohols. We commenced our catalytic study using p -toluenesulfonic acid ( p -TSA) as a homogeneous catalyst for the hydrolysis of N -benzyl spiro-epoxyoxindole as a model substrate using dry acetonitrile at 50 °C ( Table 1 , Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The construction of tertiary alcohols bearing different carbon substituents is challenging and has a potential role in biological applications. 50,51 With this in mind, we are interested in studying the hydrolytic ring-opening of spiro-epoxyoxindoles that lead to the formation of differently substituted alcohols. We commenced our catalytic study using p -toluenesulfonic acid ( p -TSA) as a homogeneous catalyst for the hydrolysis of N -benzyl spiro-epoxyoxindole as a model substrate using dry acetonitrile at 50 °C ( Table 1 , Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the plethora of examples for the DKRs of secondary alcohols, the application to tertiary alcohols is still in its infancy. Remarkably, Akai, Gröger, and co-workers have recently described the use of the oxovanadium catalyst [VO­(OSiPh 3 ) 3 ] immobilized on mesoporous silica (V-MPS4) and the Candida antarctica lipase type A (CAL-A) for the performance of the first example of DKR over these highly hindered substrates . In fact, the reactivity of racemic 1-methyl-1,2,3,4-tetrahydronaphthalen-1-ol with vinyl acetate was exhaustively analyzed considering different parameters such as the catalyst type, temperature, and solvent, finding the occurrence of the DKR process.…”
Section: Metal–enzyme Cascades Using Individual Catalystsmentioning
confidence: 99%
“…Recently, tertiary alcohols have been reported to undergo complete and selective racemization in the presence of an acidic resin material, but no data are available about the combination with a lipase [42]. Remarkably, in 2020 Akai and Gröger found that V-MPS triggered the racemization of (S)-1,2,3,4-tetrahydronaphthalene-1-ol (25 • C, 24 h, 44%→16% ee) [43]. The co-catalyzed DKR of the tertiary alcohol in the presence of CAL-A from Candida antartica lipase A and vinyl acetate led to the desired (R)-acetate in 77% yield and excellent ee value (>99%) (Scheme 8).…”
Section: Dkr Of Alcohols Co-catalyzed By Heterogeneous Catalysts (V Pd)mentioning
confidence: 99%